Specification of the Technology for Neoclassical Investment Theory: Testing the Adjustment Costs Approach - Galeotti, Marzio (The Review of Economics and Statistics, 1990)
Marzio Galeotti, Specification of the Technology for Neoclassical Investment Theory: Testing the Adjustment Costs Approach, The Review of Economics and Statistics, Vol. 72, No. 3 (Aug., 1990), pp. 471-480